PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PANKOTEKA MATERI PERSILANGAN MONOHIBRID DAN DIHIBRID PADA PESERTA DIDIK KELAS IX D SMP NEGERI 3 PULOSARI SEMESTER II TAHUN PELAJARAN 2015/2016 - Indah Palupi (Universitas PGRI Semarang, 2016)
The reseach is based on the lack of activity and the result IPA in the learning process. The purpose of this reseach is to discribe of learning process, to know the change of spiritual attitude and social attitude, to know about increasing of knowledge and knowing about increasing of skill value of studens implementate PBL model using pankoteka media of subject monohybrid and dihybrid cross to the students of SMP Negeri 3 Pulosari class IX D semester II academic year 2015/2016. The reseach action is held by two cycles.The result of reseach has showed that learning process has increase showed by increasing of activity aspect and students participation 30,3%. The change of spiritual attitude has increase to 3,03% and 100% of students have reach to criteria “B” minimize. The dicipline attitude increase 6,06%, the responsibility attitude increase to 3,03% and the confident attitude increase to 9,09%. While the value of knowledge increase to 21,20% with final clasical reach to 90,90%. The skill value of students increase to 21,21% with final clasical reach to 93,94%. Key word : activity and learning result, Problem Based Learning, Pankoteka media